Near‐Term Cerebroplacental Doppler, Heart Morphology, and Neonatal Biometry in Hypoplastic Left Heart Syndrome. (29th November 2021) - Wójtowicz, Anna; Ochoda‐Mazur, Agnieszka; Mroczek, Tomasz; Huras, Hubert; Włoch, Agata
Abstract : Objectives: To analyze near‐term cerebroplacental Doppler, heart morphology, and neonatal biometry in isolated hypoplastic left heart syndrome (HLHS) relative to healthy controls. Methods: This retrospective study included 55 fetuses with HLHS (29 with mitral valve stenosis [MS]/aortic valve atresia [AA], 14 with MS/aortic valve stenosis, and 12 with mitral valve atresia [MA]/[AA]) diagnosed prenatally between 2010 and 2019 at 2 referral centers and 101 healthy controls. Ultrasound assessment included umbilical artery (UA), middle cerebral artery (MCA) pulsatility index (PI), and cerebroplacental ratio (CPR), with neonatal weight, length, head circumference (HC), Apgar score, and UA pH measured at birth. Results: In total, 32.7% of HLHS fetuses had abnormal MCA‐PI and UA‐PI, and 38.2% had CPRs below the fifth percentile before birth. All tested Doppler parameters differed from those of the healthy controls ( P  ≤ .01). Birth weight and length were comparable between HLHS and control fetuses, whereas birth HCs were smaller in the HLHS group than in the control group ( P  = .018). In both groups, increased UA‐PI correlated with lower birth weight, but only HLHS fetuses with UA‐PI > the 95th percentile had a lower median HC at birth than those with normal UA‐PI ( P  = .045). The median UA‐PI percentile was higher in fetuses with MA than in fetuses with MS ( P  = .015). The ascending aortic diameter correlated with birth weight ( P  = .036) and birth length ( P  = .039). Conclusion: Abnormal cerebroplacental hemodynamics are evident in a high percentage of near‐term fetuses with HLHS, and increased placental resistance may contribute to birth weight and HC. Moreover, heart morphology may impact placental circulation and neonatal biometry.